Social Network “TEPAK” - Aguado Velázquez, Daniel; Algovia García, Angel; Juarranz Patiño, María (Τμήμα Ηλεκτρολόγων Μηχανικών και Μηχανικών Ηλεκτρονικών Υπολογιστών και Πληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
TEPAK Students Clubs is an application which can be use in different devices (computer, tablets, smart-phones ). It was developed with technologies based on responsive design as Jquery other technologies used are HTML5 , CSS, AJAX, PHP and mySQL , this technologies will be explained in the following chapters. TEPAK Students Clubs is a social network developing to make easier the communication among the students, is not necessary be joined with a group to use it, the only requirement is have a TEPAK account to log in.
Keywords: TEPAK; Students Clubs; Social Network; ΤΕΠΑΚ; Όμιλος Φοιτητών; Κοινωνικά Δίκτυα